Exercise with TENS does not augment gains in balance and strength for dancers. (February 2021) - Davis, Leah A.; Carzoli, Joseph P.; Feka, Kaltrina; Nelson, Christina; Enoka, Roger M.
Abstract: Electrical stimulation modulates sensory feedback and improves motor performance, at least for individuals with compromised sensorimotor function. The purpose of this study was to determine the effectiveness of a 4-wk intervention with transcutaneous electrical nerve stimulation (TENS) at improving strength and balance in dancers. Nineteen dancers completed a timed, single-leg balance test, the Y-balance test, and contractions with the hip flexor and knee extensor muscles to assess maximal strength and force steadiness. They completed 4-wks of moderate-intensity bodyweight exercises (3x/wk) and were pseudo-randomized to either a Treatment or Sham group in a single-blind design. The Treatment group received constant TENS over the hamstring muscles during the exercises, whereas the Sham group was exposed to a brief TENS current. The data were pooled due to few significant between-group differences from before to after the intervention. Most outcome measures significantly improved: hip extensor muscles were stronger ( P  ≤ 0.01), time stood on a single-leg with eyes closed increased ( P  = 0.02), and the distance reached during the Y-balance test increased ( P  ≤ 0.001). The improvement in scores on the Y-balance test exceeded the minimal clinically significant change. Twelve sessions of moderate-intensity bodyweight exercises improved muscle strength and balance in experienced dancers. The addition of TENS, however, did not augment the gains in function.